2001
DOI: 10.1091/mbc.12.12.4054
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Flux Mediates Poleward Motion of Acentric Chromosome Fragments during Meiosis in Insect Spermatocytes

Abstract: We applied a combination of laser microsurgery and quantitative polarization microscopy to study kinetochore-independent forces that act on chromosome arms during meiosis in crane fly spermatocytes. When chromosome arms located within one of the half-spindles during prometaor metaphase were cut with the laser, the acentric fragments (lacking kinetochores) that were generated moved poleward with velocities similar to those of anaphase chromosomes (ϳ0.5 m/min). To determine the mechanism underlying this poleward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 49 publications
5
73
0
Order By: Relevance
“…ochore microtubule length, then that force could act as a positional cue to direct chromosome alignment because the spindle equator would be the position where poleward traction forces would be equal between the poles. We favor this model because poleward microtubule flux is a conserved feature of spindles in most cell types (Mitchison, 1989a;Mitchison and Salmon, 1992;Desai et al, 1998;LaFountain et al, 2001;Brust-Mascher and Scholey, 2002;Maddox et al, 2002) and NuMA is localized at spindle poles, the likely position of factors needed to generate poleward microtubule flux (Waters et al, 1996). Furthermore, by examining multivalent chromosome position and kinetochore microtubule lengths in grasshopper spermatocytes, Hays et al (1982) concluded that "the magnitude of traction force on a kinetochore fiber is a linear function of fiber length."…”
Section: Chromosome Alignmentmentioning
confidence: 99%
“…ochore microtubule length, then that force could act as a positional cue to direct chromosome alignment because the spindle equator would be the position where poleward traction forces would be equal between the poles. We favor this model because poleward microtubule flux is a conserved feature of spindles in most cell types (Mitchison, 1989a;Mitchison and Salmon, 1992;Desai et al, 1998;LaFountain et al, 2001;Brust-Mascher and Scholey, 2002;Maddox et al, 2002) and NuMA is localized at spindle poles, the likely position of factors needed to generate poleward microtubule flux (Waters et al, 1996). Furthermore, by examining multivalent chromosome position and kinetochore microtubule lengths in grasshopper spermatocytes, Hays et al (1982) concluded that "the magnitude of traction force on a kinetochore fiber is a linear function of fiber length."…”
Section: Chromosome Alignmentmentioning
confidence: 99%
“…The general rule that kinetochores lead while chromosome arms follow applies in many cell types including vertebrates [7] and yeasts [8], but there are exceptions, such as in plant endosperm [9], and in crane-fly spermatocytes [10], where arms sometimes lead. These alternative cases remind us that forces are also exerted directly on chromosome arms, although the primary motive forces for anaphase are commonly exerted at kinetochores.…”
Section: Centromeres and Kinetochores Usually Lead Anaphase Movementsmentioning
confidence: 99%
“…In a more biologically successful project, Forer (1965) combined a UV microbeam and polarization light microscopy to show that once severed, spindle (kinetochore) fibers in the cranefly spermatocyte regrew from the chromosome to the spindle pole. These original experiments have since been repeated on more than one occasion, although on different cell types, with increasingly sophisticated UV and then visible laser microbeams (LaFountain, Jr., et al, 2001;Maiato et al, 2004;Spurck et al, 1990).…”
Section: B the Middle Years: Laser-based Microirradiationmentioning
confidence: 99%
“…In a more biologically successful project, Forer (1965) combined a UV microbeam and polarization light microscopy to show that once severed, spindle (kinetochore) fibers in the cranefly spermatocyte regrew from the chromosome to the spindle pole. These original experiments have since been repeated on more than one occasion, although on different cell types, with increasingly sophisticated UV and then visible laser microbeams (LaFountain, Jr., et al, 2001;Maiato et al, 2004;Spurck et al, 1990).The ability to visualize and thus target for destruction of many intracellular organelles resurrected biologist's interest in micro-photo-surgery. However, it immediately became apparent that there was a major problem of using lampgenerated UV light for this approach: since chromatin (DNA) effciently absorbs 280-nm light, all cellular systems are extremely sensitive to UV, which leads to unavoidable nonspecific (and not always easy to define) side effects (reviewed in Khodjakov et al, 1997b).…”
mentioning
confidence: 99%
See 1 more Smart Citation